General practitioner supply: family physician program and medical workforce - Faranak Farzadi; Kazem Mohammad; Farzaneh Maftoon; Reza Labbaf Ghasemi; Noorsadat Tabibzade Dezfoli (Payesh, 2009)
Payesh2009; 8: 415-421Accepted for publication: 29 September 2009[EPub a head of print-19 October 2009] Objective(s): Iranian Ministry of Health and Medical Education (MOHME) decided to implement Family Physician Program (FPP) all across the country in 2005. Workforce supply is among essential factors in most implementation projects. The aims of this study were to estimate General Practitioner Supply in Iran, and workforce adequacy analysis of FPP.Methods: This study estimates "General Practitioner Supply" based on stocks and flow model and "Required General Practitioner" based on the policies, health care delivery programs and population.Results: Implementation of FPP for whole population of Iran requires 32769 practitioners while according to the results of this study supply of general practitioners are about 28200.Conclusion: General practitioner supply is especially important in implementation of FPP. Currently, the program is implemented at rural level and in the cities with less than 20000 populations and the following step is expanding it throughout the country.The results of this study show that there is an obvious shortage around 4600 in general practitioners. Moreover the current experiences demonstrate that the recruiting and maintaining of general practitioners have not been successful in recent years. However, FPP expansion needs reassessment of population patterns receiving the service, and requires innovations to recruite and maintain practitioners.